Deep learning for pose-invariant face detection in unconstrained environment - Shivkaran Ravidas; M. A. Ansari (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In the recent past, convolutional neural networks (CNNs) have seen resurgence and have performed extremely well on vision tasks.  Visually the model resembles a series of layers each of which is processed by a function to form a next layer. It is argued that CNN first models the low level features such as edges and joints and then expresses higher level features as a composition of these low level features. The aim of this paper is to detect multi-view faces using deep convolutional neural network (DCNN). Implementation, detection and retrieval of faces will be obtained with the help of direct visual matching technology. Further, the probabilistic measure of the similarity of the face images will be done using Bayesian analysis. Experiment detects faces with ±90 degree out of plane rotations. Fine tuned AlexNet is used to detect pose invariant faces. For this work, we extracted examples of training from AFLW (Annotated Facial Landmarks in the Wild) dataset that involve 21K images with 24K annotations of the face.